Analisis Koefisien Kekentalan Fluida pada Berbagai Merek Minyak Goreng Menggunakan Tracker - Aisen Odnikana Setyanamurwan; Irnin Agustina Dwi Astuti; Endang Suhendar (UNIVERSITAS INDRAPRASTA PGRI, 2022)
This research aims to know the value of viscosity coefficient on the four cooking oil samples carried out by the video analysis using software tracker and comparing the viscosity coefficient value obtained with the viscosity coefficient value from the previous research. Determination of the viscosity coefficient of cooking oil using the falling ball mehod using a 1000ml glass tube and using marbles as solid balls. A recording is started when falling marbles from the oil surface and stops when marbles arrive on the tube base. Then, a video that was obtained was entered into a software tracker for the next step to retrieve time and distance data. Based on analysis and calculations, the study can be concluded that the viscosity coefficient value in the four cooking oil samples is brand 1 of (0.4602 ± 0.0930) Pa.s; brand 2 of (0.4246 ± 0.08665) Pa.s; brand 3 of (0.4231 ± 0.08652) Pa.s; and brand 4 of (0.4199 ± 0.08738) Pa.s.